About the freedom of the press in Italy. Berlusconi’s conflict of interests and his influence on the democracy of the ‘Bel Paese’ - González Cortés, María Eugenia (Estudios sobre el Mensaje Periodístico, 2012)
Freedom of the press in Italy is in a peculiar situation resulting from a conflict of interests concentrated on the person of his Premier, Silvio Berlusconi, the pressures exerted by mafia clans and the limited pluralism as a result of a strong media concentration. This article analyzes the health of Italian democracy and difficulties and benefits of the practice of journalism. Through deep interviews to correspondents Miguel Mora (El País), Irene Hernández (El Mundo), Gloria Moreno (Europa Press), Juan Lara (Efe), Antonio Pelayo (Antena 3) and Paloma Gómez Borrero (Cope) the article tries to reflect what means being a journalist in Italy from the perspective of Spanish professionals settled in Rome. It also includes opinions of journalists of the agency Ansa and Rai.
Keywords: Freedom of the press; journalists in Italy; right to information; freedom of speech; Silvio Berlusconi